LEGAL REGULATION OF STATE SUPERVISION (CONTROL) OF ECONOMIC ENTERPRISE ECONOMIC ACTIVITIES - Мілімко, Лариса Василівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
Purpose: to analyze the legal regulation of supervision (control) over the economic activities of aviation enterprises as business entities in Ukraine, to identify problems and establish features; outline the range of entities that exercise state control over the activities of aviation enterprises. Methods: the study was conducted using such methods as analysis, synthesis, comparison, extrapolation. Discussion: the peculiarities of state supervision (control) over the economic activity of aviation enterprises are substantiated. Results: generalized results of the reform of the sphere of control over economic activity, including aviation enterprises, the system of bodies carrying it out is determined, the legal characteristic of the pilot module of the integrated automated system of state supervision (control) is given. With the introduction of market relations in Ukraine, it is noted that economic activity should be based on such legal principles that provide for minimal influence of the state on the activities of economic entities. At the same time, it is impossible to remove economic activity from state influence and control. The author concludes that the radical changes that have taken place in the field of state supervision (control) over economic activity with the adoption of the Law of Ukraine «On Amendments to the Law of Ukraine» On Basic Principles of State Supervision (Control) in Economic Activity «supervision (control) in the field of economic activity» of November 3, 2016 № 1726-VІІІ and the introduction of the IAS DNA inspection portal, had a significant impact on improving law and order in the economic sphere, including in the field of aviation enterprises. These are the first significant steps towards the digitalization of the control function of government agencies.